2021
DOI: 10.1063/5.0062056
|View full text |Cite
|
Sign up to set email alerts
|

Homoepitaxial β-Ga2O3 transparent conducting oxide with conductivity σ = 2323 S cm−1

Abstract: Conductive homoepitaxial Si-doped β-Ga2O3 films were fabricated by pulsed laser deposition with an as-deposited 2323 S cm−1 conductivity (resistivity = 4.3 × 10−4 Ω-cm, carrier concentration = 2.24 × 1020 cm−3, mobility = 64.5 cm2 V−1 s−1, and electrical activation efficiency = 77%). High quality homoepitaxial films deposited on commercial (010) Fe-compensated β-Ga2O substrates were determined by high-resolution transmission electron microscopy and x-ray diffraction. The β-Ga2O3 films have ∼70% transparency fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…265,267,268 Based on this, homogeneous epitaxial doped b-Ga 2 O 3 films on Fe doped semi-insulating substrates have many advantages compared with heterogeneous epitaxial doped b-Ga 2 O 3 films, e.g., smooth surface (RMS o 0.5), high carrier concentrations (B10 20 cm À3 ) and electrical conductivity (m max = 2323 cm 2 V À1 s À1 ), low defects, good lattice match with the substrates, etc. 269 Therefore, homogeneous epitaxial thin films based on Fe doped semi-insulating substrates are widely applied in power devices. In addition, selecting the appropriate gate oxide dielectric material is crucial in the applications of FETs, because the lattice mismatch existing between the gate dielectric layer and the Ga 2 O 3 channel layer may further deteriorate the electronic performance of the interface.…”
Section: Mgmentioning
confidence: 99%
“…265,267,268 Based on this, homogeneous epitaxial doped b-Ga 2 O 3 films on Fe doped semi-insulating substrates have many advantages compared with heterogeneous epitaxial doped b-Ga 2 O 3 films, e.g., smooth surface (RMS o 0.5), high carrier concentrations (B10 20 cm À3 ) and electrical conductivity (m max = 2323 cm 2 V À1 s À1 ), low defects, good lattice match with the substrates, etc. 269 Therefore, homogeneous epitaxial thin films based on Fe doped semi-insulating substrates are widely applied in power devices. In addition, selecting the appropriate gate oxide dielectric material is crucial in the applications of FETs, because the lattice mismatch existing between the gate dielectric layer and the Ga 2 O 3 channel layer may further deteriorate the electronic performance of the interface.…”
Section: Mgmentioning
confidence: 99%
“…Instead, using extrinsic dopants including Si and Sn is more efficient to obtain highly conductive Ga 2 O 3 films. [8][9][10][11][12][13][14] To date, a majority of research efforts have been devoted to achieving large n-type conductivity of Ga 2 O 3 heteroepitaxial films. For example, Si-doped Ga 2 O 3 films can be deposited on foreign (MgAl 2 O 4 , sapphire) substrates by various methods such as pulsed laser deposition (PLD), [15,16] hydride vapor-phase epitaxy (HVPE), [17] and low-pressure chemical vapor deposition (LPCVD).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, using extrinsic dopants including Si and Sn is more efficient to obtain highly conductive Ga 2 O 3 films. [ 8–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ga 2 O 3 thin films prove to be a promising material for solar-blind photodetectors due to its large bandgap and UVC absorption [23], transparent electrodes for optical devices [24,25], gas sensors [26], and high-power Schottky barrier diodes with breakdown field exceeding 1 kV [27]. Moreover, Hwang et al [28] demonstrated the first high-voltage transistor based on β-Ga 2 O 3 nanomembranes exfoliated from bulk crystals.…”
Section: Introductionmentioning
confidence: 99%